Silk protein discoidal microparticles for site-specific delivery of docetaxel in metastatic lung cancer - Hyeyoun Cho; Sanghyo Park; Jun Young Park; Yoonho Hwang; Won Jun Kang; Jaehong Key (Materials Today Bio)
Silk proteins, such as silk sericin (SS) and silk fibroin (SF), have been shown to exhibit excellent biocompatibility, biodegradability, and low immunogenicity as drug delivery carriers. SS possesses antioxidant and anticancer adjuvant properties, whereas SF provides mechanical strength and structural stability, marking them as optimal materials for drug delivery systems. In this study, 3 μm discoidal silk protein particles (DSPs) based on silk sericin/silk fibroin (SS/SF) composites were developed for the loading of docetaxel (DTX). A comprehensive analysis was conducted to assess the morphological characteristics, particle size, zeta potential, drug loading content, and colloidal stability of the particles. In vitro studies utilizing human-derived non-small cell lung cancer (A549) and mouse-derived squamous cell carcinoma (SCC7) cell lines revealed that DTX-SS/SF-DSPs exhibited superior anticancer activity compared to both free DTX and DTX-SF-DSPs. In vivo biodistribution studies revealed that DTX-SS/SF-DSPs effectively accumulated in the lungs, with minimal accumulation in non-target organs, including the liver and kidneys. Anticancer efficacy evaluations showed a significant reduction in the number of tumor nodules and improvement in survival rates. Furthermore, histopathological analysis confirmed reduced inflammatory responses and the absence of major organ toxicity, demonstrating excellent biocompatibility. In conclusion, SS/SF-DSPs are a promising drug delivery system that can improve the therapeutic efficacy of anticancer drugs with minimal side effects, which can present a new paradigm in lung cancer treatment.